A Concept Towards Automated Reconstruction of Topology Optimized Structures Using Medial Axis Skeletons - Mayer, Johannes; Wartzack, Sandro (Proceedings of the Munich Symposium on Lightweight Design 2020, 2021)
Through continuous topology optimization the design within modern product development of structural loaded components can be enhanced by using maximized lightweight potential. At the same time the product development pro-cess is accelerated due to a reduced number of design cycles. Because topology optimization yields an optimized material distribution, the designer is not re-quired anymore to iteratively work out the principal geometric shape. How-ever, optimized material distribution itself neither follows design rules, nor does it pro-vide parametric relations within parts. Instead, a redesign has to be done in order to fulfill manufacturing requirements and to obtain a parametric CAD-model. This usually takes a lot of effort in time and expert knowledge. For the reason of a consistent development approach under assistance of com-puter aided methods, a concept is presented, that is demanded to solve the task of redesigning topology optimization results in parametric CAD-models in a semi-automated manner. To achieve this, medial axis skeletons are used for analyzing the geometric data of optimization results. In a second step, the skeletons are used for rebuilding parametric CAD-models. They are taken as references for common CAD-functionality whereby a parametric and history based modeling structure are generated.<br
Keywords: Topology Optimization; Medial Axis Skeleton; CAD

A New Design Method for Generating Surrogate Kinematic Truss Orthoses to support Pathological Gait Patterns in Human Model Simulations - Steck, Patrick; Scherb, David; Mayer, Johannes; Jäger, Michael; Miehling, Jörg; Völkl, Harald; Wartzack, Sandro (Proceedings of the Design Society, 2023)
With increasing life expectancy, the risk of diseases of the central nervous system, such as cancer,strokes, etc., also increases. Strokes often result in injury to the sciatic nerve, which is responsible forcontrolling the calf muscles (plantar and dorsal flexors). A so-called ankle joint orthosis (AFO) helps tosupport the pathological gait and to avoid foot drop during gait. Passive orthoses are of particularimportance for research, as they do not require additional incoming energy from outside to the orthoticsystem. However, current passive orthoses are often not personalized. On the one hand, because theyusually have only a temporary muscle-building function and, on the other hand, because the individualdesign process is computationally time consuming and thus expensive. This paper presents a possibilityto pre-dimension and pre-design passive orthoses fast and cost-efficiently by reducing the complexityof the model based on volume-optimized truss elements. Therefor a traditional high calculation intensivedesign procedure is compared with the complexity reduced model to show its effectiviness and thesimilarity of the results. Witl incoming energy from outside to the orthoticsystem. However, current passive orthoses are often not personalized. On the one hand, because theyusually have only a temporary muscle-building function and, on the other hand, because the individualdesign process is computationally time consuming and thus expensive. This paper presents a possibilityto pre-dimension and pre-design passive orthoses fast and cost-efficiently by reducing the complexityof the model based on volume-optimized truss elements. Therefor a traditional high calculation intensivedesign procedure is compared with the complexity reduced model to show its effectiviness and thesimilarity of the results. <br
Keywords: Orthoses; User centred design; Lightweight design; Truss optimization; Design methods

Computational Geometry Reconstruction from 3D Topology Optimization Results: A New Parametric Approach by the Medial Axis - Mayer, Johannes; Wartzack, Sandro (Computer-Aided Design and Applications, 2023)
Topology Optimization (TO) is used to develop high strength, yet lightweight structural components. The geometry reconstruction from raw optimization results is a crucial task and especially challenging to do considering product development’s demand on parametrics. In this paper a new automated approach for computational reconstruction is presented that uses the Medial Axis for abstraction and inclusion of parametrics and features in the reconstruction. The presented method is both highly automated and at the same time offers optional geometry editing within the reconstruction itself. The steps of the method are (1) analysis of the TO result by the Voronoi computed Medial Axis Transform, (2) processing of the Medial Axis Transform into a decomposition, and (3) redesign thereon. Directly usable files of Computer-Aided Design (CAD) are generated. The concept is presented at real world case studies with focus on non-beam-like, structural component
Keywords: Topology Optimization; Computer-Aided Design; Computational Design; Geometry Reconstruction; Skeletonization; Medial Axis Transformation

Effiziente Geometrierekonstruktion nach Topologieoptimierung eines Motorhalters - Mayer, Johannes; Sippl, Christian; Hufnagel, Thomas; Wartzack, Sandro (Konstruktion, 2024)
Topologieoptimierung (TO) kann Ausgangspunkt für effizienten Materialeinsatz und hochperformante Leichtbaukomponenten sein. Hierfür ist nach der TO eine Rekonstruktion der Geometrie in einem eigenen Prozessschritt nötig. Insbesondere wenn das Optimierungsergebnis nicht als abstraktes Oberflächenmodell, sondern als parametrische Computer-Aided-Design-(CAD)-Geometrie in den Entwicklungsprozess zurückgeführt wird, ist die Rekonstruktion arbeits- und zeitintensiv. Dieser Artikel beschreibt die Anwendung einer neuen, featurebasierten Forschungsmethode an einem Motorhalter von MAN. Statt aufwändiger Gestaltungszyklen unterstützt die Methode durch Automatisierung und Parametri
Keywords: Topologieoptimierung; Geometrierückführung; Computational Design; Generatives Design; Computer Aided Design

Effiziente Geometrierekonstruktion nach Topologieoptimierung eines Motorhalters - Mayer, Johannes; Sippl, Christian; Hufnagel, Thomas; Wartzack, Sandro (Konstruktion, 2024)
Topology optimization (TO) can be the starting point for efficient material use and high-performance lightweight components. However, a reconstruction of the geometry in a separate process step is necessary after TO. Especially if the optimization result is not considered in the development process as an abstract surface model but as parametric computer-aided design (CAD) geometry, the reconstruction is laborand time-intensive. In contrast, this article discusses the application of a new feature-based research method to an engine bracket from MAN. Instead of elaborate design cycles, the method supports automation and parametrics.
CRIS-Team Scopus Importer:2024-11-22

Ermittlung eines Skelettierungsverfahrens zur Konvertierung von Topologieoptimierungsergebnissen - Mayer, Johannes; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X (DFX2020), 2020)
By showing where to place material in a specified design space, the continuous topology optimization is very useful in product development of structural loaded components. However the optimizations design proposal is far from being a parametric CAD-model. Instead it usually consists of a tesselated surface, that has to be re-engineered. As this is often done manually, it takes a lot of time and expert knowledge. Curve skeleton algorithms have proven their ability to support the restructuring of truss-like design proposals by providing references for construction elements. To investigate a similar design concept for general optimization results, showing truss-like structures as well as surface-like sections, the suitability of surface skeletons for topology reconstruction is examined.<br
Keywords: Computational Geometry; Topology Optimization; Medial Axis Transform; Surface Skeleton

Feature-Based Reconstruction of Non-Beam-Like Topology Optimization Design Proposals in Boundary-Representation - Mayer, Johannes; Völkl, Harald; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
Geometry reconstruction from 3D topology optimization results to Computer Aided Design (CAD) is challenging, especially for automation and non-beam-like geometry. While the optimized model has polygonal format, product development with CAD requires analytical surfaces in Boundary Representation (B-Rep). In this paper, we present two approaches for an automated interpretation of surface-skeletons for CAD-reconstruction. This includes the question, when to convert the skeleton’s polygonal to analytical surfaces and how to conceptually incorporate CAD- features. One approach is based on decomposing the input in analytical, the other in polygonal surfaces. Both approaches work with specific skeleton-features and lead to a CAD-model with B-Rep-reconstruction. Exemplary results are presente
Keywords: Topology Optimization; Computer Aided Design; Geometry Post-Processing; Medial Axis Transform; Skeletonization

Fully Automated Reconstruction of Topology Optimization Results with Feature Transformation and Curve Skeletonization! - Denk, Martin; Mayer, Johannes; Wartzack, Sandro (20. VDI-Kongress mit Fachausstellung SIMVEC, Aktuelle Herausforderungen bei der Auslegung und Absicherung von Fahrzeugsystemen, 2022)
The results of a topology optimization are oft en available as so-called dead geometry in the form of cell models or polygon meshes. This fo rmat can be derived directly from finite element meshes, but no feature-based CAD parametric is available. In this work, such results are automatically transformed into a be am parametric via so-called curve skeletons. However, the curves start within the geometry and often have to be manually extruded onto the surface. In this work, this skeletonization is modified so that the individual curves usefully begin at the surface. The improved approach is then tested on a variety of model
Keywords: Skeletonization; Topology Optimization; Reconstruction; Feature Transformation

Investigation of surface skeletonization methods for reconstruction of topology optimized structures - Mayer, Johannes; Wartzack, Sandro (Proceedings of the 31st Symposium Design for X, DFX 2020, 2020)
By showing where to place material in a specified design space, the continuous topology optimization is very useful in product development of structural loaded components. However the optimizations design proposal is far from being a parametric CAD-model. Instead it usually consists of a tesselated surface, that has to be re-engineered. As this is often done manually, it takes a lot of time and expert knowledge. Curve skeleton algorithms have proven their ability to support the restructuring of truss-like design proposals by providing references for construction elements. To investigate a similar design concept for general optimization results, showing truss-like structures as well as surface-like sections, the suitability of surface skeletons for topology reconstruction is examined.
CRIS-Team Scopus Importer:2021-04-19
Keywords: Computational Geometry; Medial Axis Transform; Surface Skeleton; Topology Optimization

Procedural Concept Design with Computer Graphic Applications for Light-Weight Structures using Blender with Subdivision Surfaces - Denk, Martin; Mayer, Johannes; Wartzack, Sandro (Proceedings of the 33rd Symposium Design for X (DFX2022), 2022)
In today's concept development, it is important to develop customer requirements in advance via prototypes with little effort. Some of these requirements can be pre-tested through virtual product development, although creating them with computer aided design (CAD) software can be time-consuming. In the context of this work, tools commonly used in animation design are adapted to the early phase of virtual product development. This is primarily to limit the time effort of prototyping in product development. However, the models must be led to non-intersecting 3D manifolds to ensure a transfer into computer aided engineering (CAE) or possible manufacturing. Therfore in this work, so-called procedural designs based on computer graphic applications are described and examined for their suitability for CAE.<br

Reconstruction of Topology Optimized Geometry with Casting Constraints in a Feature-Based Approach - Mayer, Johannes; Denk, Martin; Wartzack, Sandro (Proceedings of the Design Society, 2023)
Topology Optimization (TO) is an established method for the development of high strength and lightweight structural components. However, its results have to be geometrically revised to obtain a computational model that meets product development requirements. Design has to be in accordance with manufacturing constraints. Geometry reconstruction therefore still is a typically manual and tedious task, but increasingly supported by computational and automated approaches. In this paper, the inclusion of a casting constraint in an automated Medial Axis based reconstruction method is presented. Since the Medial Axis provides cross-section values by the computation of maximally inscribed spheres, this information is used for geometry reconstruction and even further for the purposeful adaption of the cross-section to match Heuver's circle method. Thereby, the directed solidification of molten material is considered. With a predefined feeder position, the demonstrator of a suspension control arm is used to show the application of the method. Resulting CAD-models are also structurally evaluated for their stiffness characteristic
Keywords: Topology Optimization; Medial Axis Transform; Computational Design Methods; Computer Aided Design (CAD); Lightweight Design

Strukturmechanische Simulation additiv im FFF-Verfahren gefertigter Bauteile - Völkl, Harald; Mayer, Johannes; Wartzack, Sandro (Konstruktion für die Additive Fertigung 2019, 2020)
Additive Fertigung ist zum etablierten Prozess geworden. Durch schichtweisen Aufbau werden nicht mehr nur Prototypen gefertigt, sondern auch Bauteile mit hohen Steifigkeits- und Festigkeitsanforderungen. Im Fused Filament Fabrication (FFF)-Verfahren gefertigte Bauteile werden schichtweise durch Extrusionspfade aufgebaut und besitzen in Pfadrichtung üblicherweise bessere mechanische Eigenschaften als quer dazu. Unterschiedliche Extrusionspfade, insbesondere im Bauteilinneren („Infills”) besitzen daher einen hohen Einfluss auf die mechanischen Bauteileigenschaften. Um diese bereits vor der eigentlichen Fertigung abschätzen zu können, wurde ein Simulationsansatz entwickelt, der ausgehend von Fertigungsinformation (G-code) ein Simulationsmodell aufbaut, welches die lokal unterschiedlichen Materialorientierungen berücksichtigt. Dieser Ansatz soll detailliert vorgestellt und anhand eines Demonstratorbauteils mit unterschiedlichen Infill-Mustern angewandt werde
Keywords: Leichtbau; Additive Fertigung; Simulation; Fused Filament Fabrication